2020
DOI: 10.1007/s13580-020-00282-2
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of forty-five cultivars as affected by bulb initiation, bulb and scale characteristics, and bulb minerals and organic compounds of intermediate-day yellow onion (Allium cepa L.) in South Korea

Abstract: We evaluated and classified forty five onion cultivars according to bulb initiation, bulb and scale characteristics, minerals and organic compounds contents, and storage quality in South Korea during 2016/2017 and 2017/2018 growing seasons. Field experiment was conducted in randomized block design with three replications. Bulb initiation ranged from 153 days after transplanting (DAT, April 2) to 177 DAT (April 26). Fresh bulb weight (FBW) and bulb index (BI) were 285.5 ± 18.5 g/ individual, 0.93 ± 0.05, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…Furthermore, the number of fleshy scales was also highly affected by genotypical differences [11,54]. Differences were found between the two accessions, according to the results from Bal et al [55], Petropoulos et al [11], and Lee et al [48]. The results from this study agree with those of Sinkovič et al [56], who found that the average number of fleshy scales was higher for plants not subjected to nitrogen fertilization.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, the number of fleshy scales was also highly affected by genotypical differences [11,54]. Differences were found between the two accessions, according to the results from Bal et al [55], Petropoulos et al [11], and Lee et al [48]. The results from this study agree with those of Sinkovič et al [56], who found that the average number of fleshy scales was higher for plants not subjected to nitrogen fertilization.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, Gererufael et al [36] found an increase in the dry matter content as the N dose increased. Furthermore, Ncayiyana et al [37], Mogren et al [13], and Lee et al [48] found significant differences in the percentage of dry matter in various cultivars of onion.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, onion cultivars responded differently to the strength of nitrogen fertilization in terms of marketable yield and total yield (Díaz-Pérez et al, 2003). In detail, bulb quality characteristics including fresh bulb weight, bulb height and diameter, dry matter and so on were highly fluctuated by onion cultivars at harvest (Lee et al, 2020). Meanwhile, potassium fertilization linearly affected plant growth characteristics, including plant height, leaf number, leaf length, bulb length, bulb diameter, and mean bulb weight (Bekele, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…일장을 조절하며 양파 구 비대에 미치는 영향력을 분석한 연구 (An and Suh, 2013)가 있었으며, 양파 주산지의 단수와 기상자료를 활용하여 공간가중패널회귀모형을 통해 단수를 추정 한 연구 (Choi and Baek, 2016b)가 있었다. 또한, 생육기 온도 상승이 극조생 양파의 생육과 구 비대에 미치는 영향 검증 (Song et al, 2017), 고온과 다습조건이 양파 생육 및 수량에 미치는 영향력 규명 (Lee et al, 2019), 양파 구 특성 및 유기물 함량 등에 따른 품종 평가 및 분류 (Lee et al, 2020) 1-수준 모형은(Eq. 1) 생육 자료의 개체 단위 모형으로, 최종 구중과 개체별 생육자료와의 회귀분석 모형이다.…”
unclassified